2021
DOI: 10.1128/mbio.02542-21
|View full text |Cite
|
Sign up to set email alerts
|

A Vimentin-Targeting Oral Compound with Host-Directed Antiviral and Anti-Inflammatory Actions Addresses Multiple Features of COVID-19 and Related Diseases

Abstract: With the Delta variant currently fueling a resurgence of new infections in the fully vaccinated population, developing an effective therapeutic drug is especially critical and urgent in fighting COVID-19. In contrast to the many efforts to repurpose existing drugs or address only one aspect of COVID-19, we are developing a novel agent with first-in-class mechanisms of action that address both the viral infection and the overactive immune system in the pathogenesis of the disease.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Our experiments suggest that an increased stability of vimentin filaments induces contractile forces, and that these forces also can be increased by the soluble fraction of vimentin. It is important to note that R491-treatment does not eliminate the vimentin ( Li et al, 2021 ; Wu et al, 2021 ). Taken together, these observations suggest that it is the dynamic turnover of vimentin filaments and/or their solubility, and not the presence of vimentin filaments per se that regulates the force exerted over cell-matrix adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments suggest that an increased stability of vimentin filaments induces contractile forces, and that these forces also can be increased by the soluble fraction of vimentin. It is important to note that R491-treatment does not eliminate the vimentin ( Li et al, 2021 ; Wu et al, 2021 ). Taken together, these observations suggest that it is the dynamic turnover of vimentin filaments and/or their solubility, and not the presence of vimentin filaments per se that regulates the force exerted over cell-matrix adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of endosomal morphology and function for SARS‐CoV‐2 entry was demonstrated in a study reporting alteration of intermediate filaments (IF) to affect both entry and egress steps of SARS‐CoV‐2 (Li et al., 2021c ) (Figure 1 ). Using the pharmacological inhibitor ALD‐491 targeting the class III IF vimentin, the authors reported reduced SARS‐CoV‐2 entry and exosomal release in cell culture‐based assays as well as mitigated disease severity and lung damage in aged mice.…”
Section: Endosomal Trafficking and Sars‐cov‐2 Entrymentioning
confidence: 99%
“…Infection alters the architecture of the ER and the network of DMVs was found to be surrounded by a ‘cage‐like’ vimentin network and pharmacological inhibition of intermediate filaments with Withaferin A reduced SARS‐CoV‐2 replication (Cortese et al., 2020 ). Of note, vimentin appears to have a dual role in the SARS‐CoV‐2 infection cycle, by contributing to viral entry (see section ‘ENDOSOMAL TRAFFICKING AND SARS‐COV‐2 ENTRY’, Figure 1 ) and egress of infectious virus particles (Li et al., 2021c ). It has been shown that newly assembled ß‐coronaviruses exit the cells using lysosomal exocytosis with lysosomes being deacidified and lysosomal enzymes inactivated (Ghosh et al., 2020 ).…”
Section: Secretion and Exosomal Trafficking In Sars‐cov‐2 Infectionmentioning
confidence: 99%
“…A link between extracellular vimentin and SARS-CoV-2 infection has been established by several studies [33,[35][36][37][38]. Vimentin (Vim) is a type III intermediate filament-forming protein and an essential cytoskeleton element.…”
Section: Extracellular Vimentinmentioning
confidence: 99%